Influence of Work Environment and Work Characteristics on Turnover Intention System with Mediation Role of Work Engagement - Dita Indriyani; Lista Meria (International Institute for Advanced Science & Technology (IIAST), 2022)
The millennial generation currently dominates human resources in the company. Millennial generation employees have many advantages, but millennials are considered less committed to their work, so they are synonymous with high turnover intentions. The research was conducted to know the effect of the work environment and job characteristics on the turnover intention with the mediating role of work engagement in millennial generation employees, work environment, and job characteristics as independent variables. Turnover intention is the dependent variable, and work engagement is a mediating variable. This study uses a survey method by distributing questionnaires where the respondents used 204 employees in the millennial generation with domiciles in the West Jakarta area. Then, the data was processed using the SEM-PLS method. The results showed that the work environment hurt turnover intention. Job characteristics do not affect turnover intention. Job engagement hurts turnover intention. The work environment has a positive effect on work engagement. Work characteristics have a positive effect on work engagement. Furthermore, work engagement mediates the relationship between the work environment and turnover intention. Job engagement also mediates the relationship between job characteristics and turnover intention.